Study on Thermal-fluid Effect of Thermal Energy Storage Tank Design in Solar Energy Applications - R. A., Bakar; Tanti, Ali; Billy, Anak Sup; Mohd Farid, Zainudin; Gan, Leong Ming (Elsevier Ltd, 2015)
The growth of technologies in energy storage has urged new proficiencies and application areas. Energy storage technologies can be varied from an electric battery to a flywheel that can results in deliverable power based on the application. These variations are a challenge to design a reliable and efficient energy storage system. The purpose of this paper is to study the thermal-fluid effect of thermal energy storage (TES) tank design. A three-dimensional modelling of TES tank was carried out using commercial computational fluid dynamics (CFD) code by differentiate the heat source temperature and heat transfer fluid (HTF) velocity. The results predict the thermal-fluid behaviour of TES tank. Since the HTF used is water, the expected outcome of the outlet temperature is in the range of 40 to 60 °C.The outlet temperature of the TES tank is compared with the experimental data. It can conclude the TES tank thermal-fluid behaviour is affected by heat source temperature and velocity HTF. The results can be further used to design dependable TES system for green energy application